Types of Interlinguistic Homonymy: A Review of Standpoints - Kaleta, Radosław (Respectus Philologicus, 2013)
This paper reviews the more important standpoints concerning interlinguistic homonymy in a broad sense. It is a comparison of various opinions published during the last 50 years by researchers from the former USSR, Slovakia, Poland, and Western Europe. The paper shows many different terms and types of interlinguistic homonymy and explains what they result from. It also examines interlinguistic paronymies, interlinguistic synonymia, and false friends. There is no single precise definition of interlinguistic homonymy—there are a lot of different definitions concerning this issue. Some researchers claim that interlinguistic paronymies and interlinguistic homonymy are the same issue. Others claim that it is impossible to describe them together, for instance in one dictionary. The opinions of researchers are various and sometimes opposed. Not everybody believes that interlinguistic homonymy really exists, leading to frequent denials of the term interlinguistic homonymy. Homonymy is an issue which usually exists within one language—not among two or three (or more) languages. Many researchers have tried to explain this topic but each of them has understood interlinguistic homonymy differently. The paper considers doctor Katarzyna Wojan from the University of Gdansk, who shows a lot of very interesting precise definitions. She uses her own terms to be more precise and to avoid being misunderstood.
Keywords: Interlinguistic Homonymy; Interlinguistic Paronymy; Interlinguistic Synonymy; False Friends; Survey